2016
DOI: 10.1159/000445075
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil Inhibits Cyclic Strain-Induced Interleukin-8 Expression in Human Umbilical Vein Endothelial Cells

Abstract: Background: Nicorandil, a mitochondrial adenosine triphosphate-sensitive potassium (mitoKATP) channel opener, exerts protective effects on the cardiovascular system. This study examined the effect of nicorandil on cyclic strain-induced interleukin-8 (IL-8) expression in human umbilical vein endothelial cells (HUVECs). Methods: Cultured HUVECs were exposed to cyclic strain in the presence or absence of nicorandil (1-10 μmol/l); we then analyzed IL-8 expression. We also assessed the effects of nicorandil on heme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Another recent example of the bidirectional activity of nicorandil can be seen in the regulation of the expression of selected genes, such as heme oxygenase-1 or interleukin-8, by nicorandil in human umbilical vein endothelial cells (HUVECs). Only some of the observed effects were reversed by 5-HD, and thus were linked to mitoK ATP activity [ 51 ]. In addition to the other openers listed above, it has also been suggested that malonate and atpenin A5, which are inhibitors of complex II, can activate mitoK ATP channels and induce cardioprotection [ 52 , 53 ].…”
Section: Modulators Of Mitochondrial Atp-sensitive Potassium Channelsmentioning
confidence: 99%
“…Another recent example of the bidirectional activity of nicorandil can be seen in the regulation of the expression of selected genes, such as heme oxygenase-1 or interleukin-8, by nicorandil in human umbilical vein endothelial cells (HUVECs). Only some of the observed effects were reversed by 5-HD, and thus were linked to mitoK ATP activity [ 51 ]. In addition to the other openers listed above, it has also been suggested that malonate and atpenin A5, which are inhibitors of complex II, can activate mitoK ATP channels and induce cardioprotection [ 52 , 53 ].…”
Section: Modulators Of Mitochondrial Atp-sensitive Potassium Channelsmentioning
confidence: 99%
“…Studies also confirmed that serum zinc levels in luteal phase of a normal menstruation cycle are particularly lower than those in follicular phase ( 44 ). Some hypotheses suggested that the reduction in serum zinc during the luteal phase may be due to estrogen levels, enhancement of interleukin-1 or regulating progesterone and prolactin activity ( 45 - 47 ). Das and Chowdhury suggested that zinc is taken up by endometrial tissue during the luteal phase to regulate progesterone and estradiol binding receptors ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced plasma levels of C-reactive protein and sE-selectin [73] Nitroglycerin No change in asymmetric dimethyl-arginine (ADMA), human soluble P-selectin, interleukin-6, tumor necrosis factor-alpha, intercellular adhesion molecule-1, and oxidized low-density lipoproteins in healthy volunteers [74] Nicorandil Increased Mst1 and p-Mst1 levels in cardiomyocytes subjected to MI injury [75] Nicorandil Inhibition of Toll-like receptor 4 (TLR4)-mediated myeloid differentiation primary response protein 88 (MyD88)-dependent nuclear factor-kappa B (NF-κB) signaling [76] Nicorandil Inhibition of cyclic strain-induced IL-8 expression [77] Nicorandil Reduced expression of 53 cytokines after percutaneous intervention in patients with coronary artery disease [78] Nicorandil Inhibition of TNF-alpha in vitro [79] Nicorandil Inhibition of the activation of NF-kappaB, expression of adhesion molecules, and cytokine production [80] Nicorandil Inhibition of TNFalpha release from lymphocytes [80] Inorganic nitrate Reduced systemic leukocyte rolling and adherence, circulating neutrophil numbers, neutrophil CD11b expression and myeloperoxidase activity [29]…”
Section: Nitroglycerinmentioning
confidence: 99%